Transport Cost Studies Rail and Road Transport - Planning Commission (Planning Commission, 1967)
The Committee on Transport Policy and Coordination while discussing the question of Transport Costs stated as under: "To establish transport costs accurately as a means to effective cost control is a necessary step even where a commodity moves only by a single mode of transport, for the effort here must be to ensure transport at the lowest cost feasible. Where the commodity moves to a destination by more than one mode of transport, for instance, to a port by road and rail or, by a rail-cum-river route, there is need to break down the various elements of cost, so that those which can be controlled or avoided may be identified.
Joint Technical Group for Transport Planning, Planning Commission
Joint Technical Group for Transport Planning, Planning Commission